Pneumoscrotum as Complication of Blunt Thoracic Trauma: A Case Report - Eftychios Lostoridis; Konstantinos Gkagkalidis; Nikolaos Varsamis; Nikolaos Salveridis; Georgios Karageorgiou; Spyridon Kampantais; Paraskevi Tourountzi; Konstantinos Pouggouras (Case Reports in Surgery)
Introduction. Pneumoscrotum is a rare clinical entity. It presents with swollen scrotal sac and sometimes with palpable crepitus. It has many etiologies. One of them is due to blunt trauma of the thoracic cage, causing pneumothorax and/or pneumomediastinum. Case Presentation. We report the case of an 82-year-old male who was transferred to the Emergency Department with signs of respiratory distress after a blunt chest trauma. A CT scan was obtained, and bilateral pneumothoraces with four broken ribs were disclosed. Subcutaneous emphysema expanding from the eyelids to the scrotum was observed, and a chest tube was inserted on the right side with immediate improvement of the vital signs of the patient. Discussion. Pneumoscrotum has three major etiologies: (a) local introduction of air or infection from gas-producing bacteria, (b) pneumoperitoneum, and (c) air accumulation from lungs, mediastinum, or retroperitoneum. These sources account for most of the cases described in the literature. Treatment should be individualized, and surgical consultation should be obtained in all cases. Conclusion. Although pneumoscrotum itself is a benign entity, the process by which air accumulates in the scrotum must be clarified, and treatment must target the primary cause.